Diseños experimentales e investigación científica = Experimental designs and scientific research. - Badii Zabeh, Mohammad Hosein; Castillo, J.; Rodríguez, M.; Wong, A.; Villalpando Cadena, Paula (Universidad Autónoma de Nuevo León, 2007)
Abstract. The basics of the experimental designs are noted. Different features of common types of experimental designs such as the completely randomized design, the randomized block design, the Latin Square design, the split plot design and the factorial design are described. Each experimental design is illustrated by an example using real data. The application of experimental designs to the scientific research is discussed.